Cost advantage of dual-chamber versus single-chamber cardioverter-defibrillator implantation. - Goldberger, Zachary; Elbel, Brian; McPherson, Craig A; Paltiel, A David; Lampert, Rachel (Journal of the American College of Cardiology, 2005)
The purpose of this study was to determine the least expensive strategy for device selection in patients receiving implantable cardioverter-defibrillators (ICDs).
Keywords: Atrial Fibrillation; Bradycardia; Cardiac Pacing, Artificial; Connecticut; Decision Support Techniques; Defibrillators, Implantable; Electric Countershock; Electrophysiology; Heart Failure; Hospital Costs; Hospitals, University; Humans; Retrospective Studies; Sick Sinus Syndrome; Treatment Outcome